EVALUASI ZONASI TAMAN NASIONAL GUNUNG MERAPI - Dian Wijayati; R Rijanta (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2020)
Mount Merapi National Park (MMNP) is located in the region of Mount Merapi. Since the beginning of its appointment, the existence of MMNP caused cotradiction and conflict between people around Merapi and other stakeholders. Its existence is considered as a threat to limit assets, access, and their activities in the utilization of natural resources to meet their needs of life. To protect natural sustainability of Mount Merapi and refers to the regulation of national park management, MMNP is managed using zoning system. The development of MMNP zoning has considered without prejudice or harm the welfare of society, both in the aspects of conservation, economic and socio-cultural. In fact there are still wide range of violations committed by the society and other stakeholders, which indicate that the zoning has not been complied with. This research aims to evaluate the effectiveness of national park management using zoning system. The method used is deductive approach with data sources obtained from primary data in the form of observations and in-depth interviews, and secondary data in the form of documents from various sources. The results of this study indicate that zoning regulations effectively regulate the activities that carried out in each zone. However, MMNP still has "homework" to resolve grass harvesting and encroachment within MMNP.